El romanticismo en los poemas: la inocencel mediodía y a mi corazón de Julio Zaldumbide - Cacay Ochoa, Wagner Estuardo (2015)
The development of research methods are used as inductive, applied it in time to read and evaluate the poetry Zaldumbide July; deductive, I used at the time of the analysis of the main components that encompasses romantic poetry of the author; the method of literary analysis, was used to identify the scope of the author's feelings defined in abstract nouns such as loneliness, melancholy and nature as the only source that holds the anguish and sorrow suffered by humans when found in your heart with happiness, coming to understand the historical context of the 1820s era when romanticism had its heyday in Europe, Latin America and Ecuador .analysis of Innocence poems The average day and my heart was July Zaldumbide general objective dimensions of Romanticism contrast with the authors of the time and can get to know the limits that man to achieve happiness; Specific objectives were: firstly discover the romantic poetry and stylistic July Zaldumbide in the different phases of the author's emotional traits; to analyze and determine critically natural, literary and idealistic elements key nuances that have made poetry Zaldumbide the sweetest expression. With the development of the research process has succeeded in describing the romantic poems in innocence; noon and my heart, July Zaldumbide and its most characteristic features, taking into account the wide variation in thoughts and feelings that affected other literary schools worldwide.